The model for the home-bound elderly care in community thought elderly care in BOK Health Promoting Hospital, Nong Thanam Sub-district, Kukawbun District, Ubon Ratchathani Province - Charoenwong, Tasawan; Leethongdee, Songkramchai; Semrum, Wirote (UBRU Journal for Public Health Research, 2020)
Manner research takes action this time have the objective for develops care old people group format sticks a house in the community by The Model for the Home-bound Elderly Care in Community though Elderly Care Giver in BOK Health Promoting Hospital, Nong Thanam Sub-district, Kudkawbun district, Ubon Ratchathani, be manner research takes action 4 pillar step, be planning, Planning, practice Action, the observation is (Observation), and reflecting, take a random from the target group be , the participant relates, public health personnel, old people and a superintendent, 119 persons amounts, pick collect manner quantity data by use the questionnaire that establishes, analyze manner quantity data by use manner statistics describes , for example , , percentage, average, the part deviates the standard, and manner statistics estimates to are, Wilcoxon Matched-pairs Signed rank test, collect data quality manner , by group conversations , and analyze manner quality data by manner substance analysis, the research result meets that, the procedure develops this time , there is 8 the step , for example, 1) the education confiscates, 2) having appointed working group 3) analysis common data 4) planning s operate 5) train to resuscitate extremely 6) old peoples s take action to take care 7) old observation peoples, follow, and 8) evaluate , and take off a lesson, later format development, meet that , participant network group , and public health personnel , there is knowledge change, participating in, and the contentment in care old people format , for old people group and a superintendent , meet that , there is knowledge change , the behavior and the contentment build [wasp] the format improve before more format development , can summarize that , side success important factor composes 1) having policy and 2) distinct development latency regulations of extremely old people continuously 3) participating in of 4) network budget participants support enough.